2021
DOI: 10.1108/jarhe-08-2020-0277
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making system for higher education university selection: comparison of priorities pre- and post-COVID-19

Abstract: PurposeUniversity selection in higher education is a complex task for aspirants from a decision-making perspective. This study first aims to understand the essential parameters that affect potential students' choice of higher education institutions. It then aims to explore how these parameters or priorities have changed given the impact of the COVID-19 pandemic. Learning about the differences in priorities for university selection pre- and post-COVID-19 pandemic might help higher education institutions focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 78 publications
(69 reference statements)
0
20
1
1
Order By: Relevance
“…Αs a result of this feeling of disconnection, students displayed behaviors of losing interest in the class, finding it hard to concentrate, feeling disengaged and finally evaluating themselves as less productive (Yang, 2021). Of particular interest is also research from the United Arab Emirates concerning the extent to which the pandemic has affected the selection of studies by students and their families, with the variables of economic cost, quality of student life and provision of on-line courses appear to be differentiated in relation to the pre-pandemic period (Nanath et al, 2021).…”
Section: Open Accessmentioning
confidence: 99%
“…Αs a result of this feeling of disconnection, students displayed behaviors of losing interest in the class, finding it hard to concentrate, feeling disengaged and finally evaluating themselves as less productive (Yang, 2021). Of particular interest is also research from the United Arab Emirates concerning the extent to which the pandemic has affected the selection of studies by students and their families, with the variables of economic cost, quality of student life and provision of on-line courses appear to be differentiated in relation to the pre-pandemic period (Nanath et al, 2021).…”
Section: Open Accessmentioning
confidence: 99%
“…However, the positive insignificant effect of cost or study fees was found in this study. This finding signified that students' university selection decision is not influenced by the cost or study fees of the university and this is contrastive with the findings by Mahdzar et al (2021) and Nanath, Sajjad and Kaitheri (2021). There are numerous study loans available that could be applied by the students to reduce their financial burdens such as National Higher Education Fund Corporation (PTPTN), Sarawak Foundation and other organizations.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, the cost of the study is expected to significantly impact the students' behaviour intention in selecting a university. This proposition is supported by Mohd Yusuf, Ghazali & Abdullah (2017), Mahdzar et al (2021) and Nanath, Sajjad and Kaitheri (2021) as the cost of study or tuition fees was significant factor or most important factor that influenced university selection. However, the insignificant effects of cost or tuitions fees towards university selection are also found in Wong (2019).…”
Section: Costmentioning
confidence: 69%
“…Recently, parallel to the increase in competition among universities, studies related to their evaluation have gained increasing attention from different perspectives such as overall performance (Aliyev et al, 2020 ; Nazari-Shirkouhi et al, 2020 ; Wu et al, 2012 ; Zolfani & Ghadikolaei, 2013 ), research capacity (Duc et al, 2020 ; Su et al, 2020 ), innovation (Chen & Chen, 2010 ), a department of a university (Muhammad et al, 2021 ), sustainability (Arora et al, 2020 ; Puente et al, 2020 ), lean philosophy (Kazancoglu & Ozkan-Ozen, 2019 ; Klein et al, 2021 ), and student viewpoint (Castro-Lopez et al, 2021 ; Goyal et al, 2021 ; Kabak & Dağdeviren, 2014 ; Nanath et al, 2021 ; Nojavan et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%